A comparative analysis of dry eye disease prevalence among undergraduate and postgraduate medical students in Darbhanga, North Bihar - Agrawal, Vironika; Kumar, Nishant; Patel, Deepak; Shahnawaz, Asif (International Journal of Research in Medical Sciences, 2026)
Background: This study aimed to compare the prevalence and severity of dry eye disease among undergraduate (UG) and postgraduate (PG) medical students in Darbhanga, North Bihar. Methods: A prospective cross-sectional study was conducted among medical students of a tertiary medical college in Darbhanga. Participants completed a structured questionnaire including demographic details, risk factors and the Ocular Surface Disease Index (OSDI). Clinical evaluation consisted of tear break-up time (TBUT) and Schirmer’s test. DED was diagnosed using OSDI scores ≥13 in combination with at least one abnormal clinical parameter. Data were analysed to compare prevalence, mean OSDI scores and associated risk factors between UG and PG groups. Results: Of the 200 participants, the overall prevalence of dry eye was 38.5%. Undergraduate students showed a significantly higher prevalence (49%) compared to postgraduate students (28%). The difference was statistically significant (χ² = 10.18, p = 0.0014). Undergraduates had 1.75 times higher risk and 2.46 times higher odds of developing dry eye than postgraduates. Conclusions: Undergraduate medical students in Darbhanga have a significantly higher burden of dry eye disease compared to postgraduate trainees. Excessive screen exposure and lifestyle habits are important contributors. Awareness programs and preventive strategies are essential to reduce the rising incidence of DED in this population.